Concepções sobre limite: imbricações entre obstáculos manifestos por alunos do ensino superior - Celestino, Marcos Roberto (2008)
This work is inserted in the research line "History, Epistemology and Teaching of Mathematics "in the process of teaching and learning of Differential and Integral Calculus. Its focus is on the conceptions of students of Higher Education levels about limits and some possible imbrications among epistemological obstacles related to such concepts. To achieve this goal, we developed our work with numerical sequences, approaching aspects of convergence and monotonicity, the relationship between terms such as "to have limits" and "to be limited". Aiming our target, we developed a set of activities taking into account the results of the researches on the term limit and epistemological obstacles identified in such researches.The subjects who took part in our research are university students who had already studied limit of a function of real variable. The group was made up of students of the fifth semester of Electrical Engineering course of a private university, located in the east area of São Paulo. The analysis of the data was made with the aid of the software C.H.I.C. (Cohesitive Implicative and Hierarchical Classification).The software C.H.I.C. allows us to extract a set of information, crossing subjects (or objects) and variable (or attributes), rules of association between variables, to provide a probabilistic index of quality of association and to represent a structure of variables in the form of hierarchical classification tree and/or in the form of an implicative graph between attributes. The analysis of the results of this survey was based on Cornu´s (1983), Sierpinska´s (1985) and Robert´s (1982) researches.Through the analysis we were able to identify evidence of possible imbrications between some obstacles and similarities and dissimilarities among the meanings that the subjects who took part in our research attributed to the expressions of limit